The Samara school of morphology. Emrullah Adyshirinovich Adyshirin-Zadeh (review article) - E. V. Samokhina; A. Yu. Adayeva; A. V. Gorshenin; A. A. Supilnikov; B. I. Yaremin; N. A. Lysov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
The present work is devoted to the study of the scientific and life path of professor anatomist Emrullah Adyshirinovich Adyshirin-Zadeh (1920–2017), one of the founders of the Samara and Russian morphological school. A review of his main scientific works and educational and methodological publications is given.